DISINFECTION PROCEDURES: THEIR EFFICACY AND EFFECT ON DIMENSIONAL ACCURACY, SURFACE QUALITY AND SURFACE DETAIL REPRODUCTION OF AN IRREVERSIBLE HYDROCOLLOID IMPRESSION MATERIAL - O'SULLIVAN, MICHAEL; COLEMAN, DAVID; O'DONNELL, MARY (My University, 2011)
Objectives: This study investigated the antibacterial efficacy and effect of 0.55% ortho-phthalaldehyde (Cidex OPA?) and 0.5% sodium hypochlorite (NaOCl) on the dimensional accuracy and surface quality of gypsum casts retrieved from an irreversible hydrocolloid impression material. Methods: A simulated clinical cast and technique was developed to compare the dimensional accuracy and surface quality changes of the test gypsum casts with controls. Dimensional accuracy measurements were completed between fixed points using a travelling microscope under low angle illumination at a magnification of X3. Surface quality changes of ?smooth? and ?rough? areas on the cast were evaluated by means of optical profilometry. The efficacy of the disinfection procedures against Pseudomonas aeruginosa was evaluated by determining the number of colony forming units (cfu) recovered after disinfection of alginate discs inoculated with 1 ? 106 cfu for defined intervals. Results: The dimensional accuracy of the gypsum casts was not significantly affected by the disinfection protocols. Neither disinfectant solution nor immersion time had an effect on the surface roughness of the ?smooth? area on the cast, however, a significant increase in surface roughness was observed with increasing immersion time for the ?rough? surface. Complete elimination of viable Pseudomonas aeruginosa cells from alginate discs was obtained after 30 and 120 s immersion in Cidex OPA? and NaOCl, respectively. Conclusions: Immersion of irreversible hydrocolloid impressions in Cidex OPA? for 30 s was proved to be the most effective disinfection procedure.
PUBLISHED
Keywords: Dental Science; dental impressions; Immunology, Inflammation & Infection